Perbandingan Strategi Pemberantasan Peredaran Narkoba di Indonesia dan Belanda - Hery Firmansyah; Grace Bernadette Michelle (CV Rewang Rencang, 2024)
Drug abuse poses a global threat to public health and social stability. Indonesia and the Netherlands face distinct challenges in combating drug trafficking, influenced by their respective cultures and legal frameworks. This study aims to compare anti-drug strategies in both countries to identify more effective approaches. A normative juridical method with a comparative approach was employed to evaluate regulations, policies, and practices. Findings reveal Indonesia's emphasis on law enforcement and rehabilitation, while the Netherlands implements a limited tolerance policy for certain drugs. Indonesia's strength lies in its strict social protection measures, but it struggles with entrenched drug distribution networks. Conversely, the Netherlands has successfully reduced heavy drug users through strict regulations in specific sectors, though illegal trade remains a challenge. In conclusion, a synergy of law enforcement and community education approaches is essential for effective drug eradication.